T helper cell-independent neutralizing B cell response against vesicular stomatitis virus: role of antigen patterns in B cell induction? - Bachmann, M; Hengartner, H; Zinkernagel, R (1995)
The neutralizing antibody response against vesicular stomatitis virus (VSV) was studied to analyze conditions necessary for induction of mature B cells. The glycoprotein of VSV (VSV-G) is expressed as repetitive epitopes that are in a rigid densely packed paracristalline form in the virus envelope; in contrast, VSV-G is present in a mobile randomly ordered form on infected cells and in micelles. We found that the rigid, paracristalline form of VSV-G spaced about 5-10 mm on VSV virons induced potent primary and secondary neutralizing B cell responses which were independent of T helper cells, whereas the more randomly distributed, mobile forms of VSV-G induced primary and secondary B cell responses that were more tightly controlled by T helper cells. These data suggest that (i) cross-linking is a critical signal for B cell activation and antibody production, and that this signal alone does not necessarily anergize or delete mature B cells, (ii) the more regularly and rigidly ordered in a distance of 5-10 nm repetitive identical antigenic determinants are, the less are primary and secondary B cell responses controlled by T cells. We therefore propose that B cells take antigen organization as a marker for foreigness.